The Impact of COVID-19 on Physical Activity and Life Satisfaction of Golfers: A Cross-Sectional Study in German-Speaking Countries - Jungwirth, David; Angerer, Martin; Haluza, Daniela (Frontiers in Sports and Active Living, 2022)
Golf is an outdoor sport played worldwide, and golfers of all ages benefit from regular exercise and social contact. The COVID-19 crisis has led to lockdowns, curfews, and closures of golf courses and other indoor and outdoor sports facilities. This study aimed to retrospectively assess how golfers perceived the impact of the crisis on physical activity and life satisfaction. We conducted a cross-sectional online survey among 1,115 golfers (61% men, mean age 55.0 years) in German-speaking countries, mainly Austria and Germany, from March to June 2021. When comparing ratings before and during the COVID-19 period, participants reported exercising more indoors at home independently or with online instructions. Likewise, the popularity of exercising outdoors in publicly accessible open spaces increased overall, especially in rural areas by about 10%. Life satisfaction decreased significantly by 24.2% (p < 0.001) during the pandemic. From a public health perspective, access to outdoor sports facilities such as golf courses might alleviate the negative psychosocial and health effects of home confinement and restricted access to indoor sports facilities. Further research is recommended to evaluate the longer-term impact of COVID-19-related measures on the physical activity and life satisfaction of golfers.